Theoretical and Epistemological Thoughts on Archaeology and Experimental Lithic Technology - Nami, Hugo Gabriel (2018)
In the wide field of archaeology, stone tool remains are one of the main pieces of evidence used for assessing knowledge and understanding of the archaeological record. To cope with its analysis and interpretation as a branch of experimental archaeology, one field of research that has become more notable is experimental lithic technology. Based on experience and development of this discipline in thesouthern cone of South America, and with the aim of contributing to the growing theoretical perspectives in this field, this paper addresses the theoretical and epistemological issues that deal with theoretical, variability, classification, and deontological concerns.